Les exercices de prospective énergétique à l’épreuve des mutations des modes de vie - Thomas Le Gallic; Edi Assoumou; Nadia Maïzi; Pierre Strosser (VertigO)
Among the tools and processes that are used to inform decisions makers on the long-term challenges raised by energy transition, prospective studies are at the forefront. This paper investigates how energy forecasting exercises take into account lifestyle changes – that constitute fundamental components of societies’ direct and indirect energy consumption. Thirteen French exercises are screened confirming that most foresight studies do not entirely consider lifestyle as a key factor. However part of recent exercises takes into consideration lifestyles as an emerging issue. Our literature review – completed by a monograph of five pioneer studies and research projects – initiates the thought about perspectives offered by lifestyle consideration in energy transition foresight exercises. Limitations associated with existing tools and models are also discussed in this paper.